A simplified scoring system in de novo follicular lymphoma treated initially with immunochemotherapy - Bachy, Emmanuel; Maurer, Matthew J; Habermann, Thomas M; Gelas-Dore, Bénédicte; Maucort-Boulch, Delphine; Estell, Jane A; Van den Neste, Eric; Bouabdallah, Réda; Gyan, Emmanuel; Feldman, Andrew L; Bargay, Joan; Delmer, Alain; et al. (Blood, 2018)
In follicular lymphoma (FL), no prognostic index has been built based solely on a cohort of patients treated with initial immunochemotherapy. There is currently a need to define parsimonious clinical models for trial stratification and to add on biomolecular factors. Here, we confirmed the validity of both the follicular lymphoma international prognostic index (FLIPI) and the FLIPI2 in the large prospective PRIMA trial cohort of 1135 patients treated with initial R-chemotherapy ± R maintenance. Furthermore, we developed a new prognostic tool comprising only 2 simple parameters (bone marrow involvement and β2-microglobulin [β2m]) to predict progression-free survival (PFS). The final simplified score, called the PRIMA-PI (PRIMA-prognostic index), comprised 3 risk categories: high (β2m > 3 mg/L), low (β2m ≤ 3 mg/L without bone marrow involvement), and intermediate (β2m ≤ 3 mg/L with bone marrow involvement). Five-year PFS rates were 69%, 55%, and 37% in the low-, intermediate-, and high-risk groups, respectively (P < .0001). In addition, achieving event-free survival (EFS) or not at 24 months (EFS24) was a strong posttreatment prognostic parameter for subsequent overall survival, and the PRIMA-PI was correlated with EFS24. The results were confirmed in a pooled external validation cohort of 479 patients from the FL2000 LYSA trial and the University of Iowa/Mayo Clinic Lymphoma Specialized Program of Research Excellence Molecular Epidemiology Resource. Five-year EFS in the validation cohort was 77%, 57%, and 44% in the PRIMA-PI low-, intermediate-, and high-risk groups, respectively (P < .0001). The PRIMA-PI is a novel and easy-to-compute prognostic index for patients initially treated with immunochemotherapy. This could serve as a basis for building more sophisticated and integrated biomolecular scores.
Keywords: Female; ženské pohlaví; přežití bez známek nemoci; Immunotherapy; lidé; Bone Marrow; Lymphoma, Follicular; beta-2-mikroglobulin; míra přežití; Antineoplastic Combined Chemotherapy Protocols; beta 2-Microglobulin; protokoly protinádorové kombinované chemoterapie; kostní dřeň; Male; imunoterapie; Aged; nádorové proteiny; Neoplasm Proteins; Survival Rate; Disease-Free Survival; folikulární lymfom; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans